EXPERIENCE OF TREATMENT WITH RITUXIMAB IN PATIENT WITH SYSTEMIC TYPE OF JUVENILE RHEUMATOID ARTHRITIS - K.B. Isaeva; E.I. Alexeeva; R.V. Denisova; T.M. Bzarova; S.I. Valieva; A.O. Lisitsin; E.Yu. Gudkova; E.L. Semikina; E.A. Kopyl'tsova (Вопросы современной педиатрии, 2009)
The article gives a case report on patient with severe systemic type of juvenile arthritis, refractory to treatment with classical immuno suppressants and blocker of tumor necrotizing factor Successive application of biological agent — rituximab was described. In 9 weeks, extra articular symptoms of disease and acute inflammatory lesions in joints were stopped, and functional activity of child increased. Presented case report demonstrates high effectiveness of rituximab: patient with severe systemic type of juvenile arthritis has clinical and laboratory remission of disease during 12 months.Key words: children, juvenile rheumatoid arthritis, rituximab.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):132-138)